Controlling groundwater over abstraction: state policies vs localpractices in the Jordan highlands - Naber, M.A. (IWA Publishing, 2017)
The control of groundwater over abstraction is a vexing problem worldwide. Jordan is one of the countries facing severe water scarcity which has implemented a wide range of measures and policies over the past 20 years. While the gap between formal legal and policy frameworks and local practices on the ground is widely acknowledged, few studies investigate how local users react to state regulations and document their tactics to circumvent them. This paper examines the major tools implemented by the Jordanian government to control well expansion and water abstraction and how farmers in the Azraq basin have responded to these measures. It then documents how, in response, the Ministry of Water and Irrigation has recently enacted a series of creative counter-measures, both direct and indirect, in an attempt to toughen law enforcement and raise pressure over groundwater users. The lessons learned are highly relevant for countries with similar situations, both in the region and elsewhere.